Development of Interactive Learning Media using Autoplay Studio 8 for Hydrocarbon Material of Class XI Senior High School - Fitriani, Okta; Susilawati, Susilawati; Linda, Roza (Journal of Educational Sciences, 2020)
Improving the quality of education can take advantage of technology that is currently increasingly advanced. The expected result, the education world is no longer awkward in using technology to improve its quality. One of the lessons that requires learning media technology is chemistry. This study aims to develop interactive learning media using Autoplay Studio 8 for Hydrocarbon material and conducting some tests to determine the response of educators and students as well. The media created were tested, including testing the feasibility based on expert validation and the responses of educators and students to the developed media. The research method used in the development of instructional media that used a research and development (R&D) approach. Overall the interactive learning media Autoplay Studio 8 developed was declared valid by a validator consisting of three material experts and three media experts with an average percentage value of media experts being 94.15%, and an average percentage of material experts 93 7%. The response of chemistry teachers and students with an average percentage score was 94.6% and 92.33% categorized as very practical. It can be concluded that media is ready to use in the real learning process.